Uinsa International Community Engagement in South Korea: A Track Record of Service, Collaboration, and Empowerment of The Indonesian Muslim Community - Arina Putri Tsania; Usfiyahturrusuli Usfiyahturrusuli; Rahma Khofifah Alawiyah; Syah Barara Nurhamidin Sidiki; Agus Afandi (FKIP, Universitas Palangka Raya, 2026)
South Korea presents multidimensional challenges for the Indonesian diaspora, particularly Indonesian migrant workers (PMI), in maintaining their Islamic identity in a secular society with a highly disciplined work culture. This article documents the implementation of the UINSA International Community Engagement (UICE) 2025 program, an initiative that integrates student mobility with community service using the Asset-Based Community Development (ABCD) approach. This research uses a descriptive qualitative method to explore the potential and assets of the community at Al-Barokah Mosque, Gimhae, which include individual, social, physical, spiritual, and economic assets. The program implementation focused on empowerment and education through mental strengthening seminars, digital da'wah (podcasts), fiqh studies for women, the establishment of a Quran Education Park (TPQ) for migrant children, and support for the mosque's economic independence (BUMM). The results of the activities show that cross-cultural interaction and this asset-based approach are effective in strengthening Islamic identity, building transnational solidarity, and empowering the PMI community to be more independent and resilient in facing social vulnerability in a minority country.